Structural changes of biocompatible neutral microemulsions stabilized by mixed surfactant containing soya phosphatidylcholine and their relationship with doxorubicin release - Formariz, T. P. [UNESP]; Chiavacci, L. A. [UNESP]; Sarmento, V. H. V. [UNESP]; Franzini, C. M. [UNESP]; Silva, A. A. [UNESP]; Scarpa, M. V. [UNESP]; Santilli, Celso Valentim [UNESP]; Egito, E. S. T.; Oliveira, Anselmo Gomes de [UNESP] (Elsevier B.V., 2008)
Depending on the composition, the mixture of surfactant, oil and water, may form supramolecular aggregates with different structures which can significantly influence the drug release. In this work several microemulsion (ME) systems containing soya phosphatidylcholine (SPC) and eumulgin HRE40 (TM) (EU) as surfactant, cholesterol (O) as oil phase, and ultra-pure water as an aqueous phase were studied. MEs with and without the antitumoral drug doxorubicin (DOX) were prepared. The microstructures of the systems were characterized by photon correlation spectroscopy, rheological behavior, polarized light microscopy, small-angle X-ray scattering (SAXS) and X-ray diffraction (XRD). The results reveal that the diameter of the oil droplets was dependent on the surfactant (S) amount added to formulations. The apparent viscosity was dependent on the O/S ratio. High O/S ratio leads to the crystallization of cholesterol polymorphs phases which restricts the mobility of the DOX molecules into the ME structure. Droplets with short-range spatial correlation were formed from the ME with the low O/S ratio. The increase of the cholesterol fraction in the O/S mixture leads to the formation of ordered structures with lamellar arrangements. These different structural organizations directly influenced the drug release profiles. The in vitro release assay showed that the increase of the O/S ratio in the formulations inhibited the constant rate of DOX release. Since the DOX release ratio was directly dependent on the ratio of O/S following an exponential decay profile, this feature can be used to control the DOX release from the ME formulations. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: microemulsion; cholesterol; lamellar structures; drug delivery; doxorubicin